Effect of Martial Arts on Swiftness Development in Middle-Schoolers - Ю. В. Голенкова; А. В. Скригін (OVS LLC, 2015)
The objective of the research is to determine the effect of taekwondo means on swiftness development in middle-schoolers. To achieve the objectives set, the research used the following methods: analysis of specialized methodological and scientific literature and other sources; pedagogical experiment; pedagogical observations; testing; methods of mathematical statistics. Conclusions: The paper grounds and develops the methods of swiftness development in middle-school pupils by taekwondo means, and experimentally verifies their effectiveness. It proves that introducing the variable module "Taekwondo" into the process of physical education of middle-schoolers can bring about improved swiftness development, in particular, such indicators as the tapping test and running in place for 5 seconds.